History and physical examination - Chan, Paul D. (Current Clinical Strategies Pub., 2001)
This useful manual contains clinical pearls and guidance for history and physical taking. It is conveniently organized by disease and symptom, and it includes a complete differential diagnosis for each disease. It is useful for medical students, residents, and physicians in practice.